Cultural, Morphological and Cross Infectivity of Lasiodiplodia Theobromae Causing Fruit Rot of Jackfruit (Journal of Plant Disease Sciences, 2023)
Jackfruit fruit rot incited by Lasiodiplodia theobromae is the most serious disease of jackfruit. The pathogen cultural and morphological characteristics, and the exploration of cross infectivity investigated. Typical symptoms of Lasiodiplodia fruit rot of jackfruit were detected in pathogenicity tests on both naturally and artificially contaminated jackfruit fruits. Small regions of brownish lesions were initially noticed on the syncarp (outer skin) of mature jackfruits, either singularly or in a scattered manner. On varied medium, Lasiodiplodia theobromae grew with a consistent degree of variance. The highest radial growth of L. theobromae (90 mm) was recorded on potato dextrose agar medium, malt extract agar medium, and host plant leaf extract agar medium, among the solid media tested. A cross-infection investigation indicated that the jackfruit pathogen L. theobromae might infect different fruits and vegetables, including banana, cashew, cocoa, guava, lemon, papaya, sapota, bread fruit, brinjal, cucumber, raddish, and tomato.
Keywords: Jackfruit; Fruit rot; Lasidiodiplodia theobromae; Cultural and Crossinfectivity